In-Vivo evaluation of implantable film containing Microencapsulated Sustained Releas Dexamethasone Sodium Phosphate - Abdul Ameer, Mohammed Wajeah; Maraie, Nidhal K.; Alwaeli, Ali Mohsin (Journal of Contemporary Medical Sciences, 2019)
Objective: This work involved in vivo evaluation of the previously prepared implantable film dosage form containing microencapsulated dexamethasone sodium phosphate (which is equivalent to 16 mg dexamethasone) and 4.4 mg pure dexamethasone sodium phosphate (which is equivalent to 4 mg dexamethasone) to be inserted at the inflamed areas to get suitable precise controlled release. Methods: the animals used were 33 rates divided into 8 groups and the inflammation was induced by using 2.0% carrageenan solution to be injected intra-dorsally then the film was inserted locally and then sacrifying the animals on different time tables to take sample from the site of inflammation for 5 months and examined under electron microscope. Results: the results showed that the prepared implantable film had immediate anti-inflammatory effect upon insertion at the inflamed tissue and its action continued effectively for five months. Conclusion: this work proved that implantable film containing dexamethasone should be used after surgery of joint replacement or any other surgery site as alternative to the applied regimen of giving IM injection of the commercially available 10mg dexamethasone intraoperatively and a second 10 mg within 24-hour postoperatively to reduce edema and pain followed by oral dexamethasone 0.5 mg on daily based till complete recovery which may last for 5 months or more and subject the patients to the serious systemic effects. The application of the implanted film therapy may reduce the rejection of the body to the replaced joint or other replacement surgery and improves patient compliance.